Challenges to Create a Global Cohesive Society in Post-Conflict Situations and Its Impact in Federal Democratic Republic of Nepal - Nepal, Bishnu Hari (Journal of APF Command and Staff College, 2018)
After Cold War, "Clashes of Civilizations" could be paramount in the coming centuries. Naturally, they will be supported by the detrimental effects of technology like the Artificial Intelligence (AI) further advanced in the 21st century in the process of the evolution of a global cohesive society. Even the space will be a playground of the mundane strategic order. Countries like Federal Democratic Republic of Nepal can play a crucial role reviving her glory of the dawn of civilization on earth as a soft-power resulted from the geo-political and strategic values utilizing modalities recommended by the author.